Sale Of Goods Law In Malaysia - Abdul Majid , Krishnan Arjunan (Duo, 2016)
Presenting an in-depth exposition of the various topics under sale of goods law in prose that is clear,concise and readable, this book makes possible agod understanding of an aspect of law that often aries in many commercial transaction.